Composite positive electrode material, preparation method thereof and all-solid-state lithium battery containing composite positive electrode material
By forming a lithium fluoride protective layer between the positive electrode active material of an all-solid lithium battery and the sulfide solid electrolyte, the battery performance limitations caused by the interface reaction are solved, and the cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202311203649.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
During the circulation process, the interface impedance of the existing all-solid lithium batteries increases due to the interface reaction between the positive electrode active material and the sulfide solid electrolyte, which limits the reversible specific capacity and cycle stability of the battery.
A lithium fluoride protective layer is formed between the positive electrode active material and the sulfide solid electrolyte, increasing the interface area and reducing the potential difference, thereby reducing interface side reactions.
By forming a lithium fluoride protective layer, the cycle stability and rate performance of all solid-state lithium batteries are significantly improved.
Smart Images

Figure CN119650608A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a composite positive electrode material, a preparation method thereof and an all-solid-state lithium battery comprising the same. Background Art
[0002] Lithium-ion batteries have been widely used in many fields, including portable electronics, electric vehicles, grid storage, etc. For future electric vehicles with high mileage, higher energy density is required, and the energy density of commercial lithium-ion batteries has reached its limit. In addition, the leakage and thermal instability of highly flammable liquid electrolytes have caused serious safety issues for commercial lithium-ion batteries. To solve these problems, all-solid-state lithium battery technology has been widely regarded as one of the most promising candidate technologies.
[0003] Sulfide solid electrolyte has 10 -3 ~10 -2 S cm -1 With high ionic conductivity, a lithium ion migration number close to 1 and good machinability, sulfides and active materials can easily form an electrolyte / electrode material interface with low interfacial impedance through a room temperature mechanical cold pressing process, and form interconnected two-dimensional ion transport channels on the interface, which will be beneficial to the assembly, preparation and performance optimization of all-solid-state batteries. Nickel cobalt manganese oxide positive electrode materials show great advantages in energy density and cycle stability due to the synergistic effect of multiple metals. Combining sulfide solid electrolytes with nickel cobalt manganese oxide positive active materials to assemble all-solid-state batteries will be a feasible strategy to achieve high-performance all-solid-state batteries.
[0004] However, the composite cathode material prepared by mixing the unmodified nickel cobalt manganese oxide cathode active material with the sulfide solid electrolyte will undergo severe interfacial reactions during the battery cycle, resulting in a sharp increase in the battery interface impedance, which in turn limits the reversible specific capacity of the all-solid-state battery and deteriorates the battery cycle stability. Although the interface side reactions of the composite cathode material prepared by mixing the coated nickel cobalt manganese oxide cathode active material with the sulfide solid electrolyte are alleviated, the poor solid-solid contact hinders ion transport, and the assembled all-solid-state lithium battery has poor rate performance.
[0005] Therefore, how to reduce the interfacial reaction between the positive electrode active material and the sulfide solid electrolyte to improve the cycle stability and rate performance of all-solid-state lithium batteries is an urgent problem to be solved in this field. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a composite positive electrode material, a preparation method thereof and an all-solid-state lithium battery comprising the same. The composite positive electrode material has a lithium fluoride layer, which can increase the interface area between the positive electrode active material and the sulfide solid electrolyte while inhibiting the interface contact reaction between the two, so that the all-solid-state lithium battery using the composite positive electrode material has good cycle stability and rate performance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a composite positive electrode material, comprising positive electrode active material particles, sulfide solid electrolyte particles and a lithium fluoride layer;
[0009] The lithium fluoride layer is located between the positive electrode active material particles and the sulfide solid electrolyte particles.
[0010] In the composite positive electrode material provided by the present invention, there is a lithium fluoride protective layer between the positive electrode active material and the sulfide solid electrolyte, which can increase the interface area between the positive electrode active material and the sulfide solid electrolyte, while reducing the potential difference between the two and reducing the interface side reactions between the two, thereby improving the cycle stability and rate performance of the all-solid-state lithium battery.
[0011] In some embodiments of the present invention, the lithium fluoride layer is coated on the surface of the sulfide solid electrolyte particles, or coated on the surface of the positive electrode active material particles, or coated on the surface of the positive electrode active material particles and the surface of the sulfide solid electrolyte particles.
[0012] In some embodiments of the present invention, the positive electrode active material is selected from one or more of nickel cobalt manganese oxide and lithium manganese oxide.
[0013] In some embodiments of the present invention, the lithium nickel cobalt manganese oxide is LiNi m Co n Mn 1-m-n O2;
[0014] Among them, 0.5≤m<1 (for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.98, etc.), 0.5≤m+n≤1 (for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.).
[0015] In some embodiments of the present invention, the sulfide solid electrolyte is selected from compound x (Li a G)·y(T c D d )·z(P2S5) or more;
[0016] Among them, 0≤x<100, 0≤y<100, 0≤z<100;
[0017] a=1 or 2, c=1 or 2, d=1, 2 or 5;
[0018] Element G is S, Cl, Br or I;
[0019] The element T is Li, Si, Ge, P, Sn or Sb;
[0020] Element D is Cl, Br, I, O, S or Se;
[0021] And Li a G.T c D d Unlike P2S5, the stoichiometric numbers of Li and S are not 0.
[0022] In some embodiments of the present invention, the mass ratio of the positive electrode active material to the sulfide solid electrolyte is (50-80):(20-50); for example, it can be 50:50, 52:48, 55:45, 58:42, 60:40, 62:38, 65:35, 68:32, 70:30, 72:28, 75:25, 78:22 or 80:20, etc.
[0023] In the present invention, if the content of sulfide solid electrolyte in the composite positive electrode material is too little, the interface area between it and the positive electrode active material is small, which will result in a low ion transmission efficiency of the composite positive electrode material; if the content of sulfide solid electrolyte is too much, the content of positive electrode active material is small, which will result in a low energy density of the all-solid-state lithium battery.
[0024] In some embodiments of the present invention, the mass of fluorine in the lithium fluoride layer accounts for 0.1-2% of the mass of the composite positive electrode material; for example, it can be 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.6%, 1.8% or 2%, etc.
[0025] In the present invention, if the fluorine content in the composite positive electrode material is too little, the lithium fluoride layer formed is small, and its corresponding effect of increasing the interface area and inhibiting the interface reaction is weak; if the fluorine content in the composite positive electrode material is greater than 2%, the lithium fluoride layer formed is already sufficient, and its effect of increasing the interface area and inhibiting the interface reaction will not be significantly improved. On the contrary, it will reduce the relative content of the positive electrode active material and reduce the energy density of the all-solid-state lithium battery.
[0026] In a second aspect, the present invention provides a method for preparing the composite positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0027] Method 1: Mixing a sulfide solid electrolyte with a fluorine-containing compound and calcining them to obtain a lithium fluoride-coated sulfide solid electrolyte; then mixing it with a positive electrode active material and calcining it to obtain the composite positive electrode material;
[0028] Alternatively, method 2: mixing the positive electrode active material with a fluorine-containing compound and calcining to obtain a positive electrode active material coated with lithium fluoride; and then mixing with a sulfide solid electrolyte and calcining to obtain the composite positive electrode material;
[0029] Or method three: the positive electrode active material, the sulfide solid electrolyte and the fluorine-containing compound are mixed and calcined to obtain the composite positive electrode material.
[0030] The present invention forms an in-situ lithium fluoride protective layer between the positive electrode active material and the sulfide solid electrolyte by calcining a fluorine-containing compound with the positive electrode active material and / or the sulfide solid electrolyte, thereby increasing the interface area between the positive electrode active material and the sulfide solid electrolyte, reducing the potential difference between the two, and reducing the interface side reactions between the two, so that the all-solid-state lithium battery using the composite positive electrode material of the present invention has good cycle stability and rate performance.
[0031] In addition, the existing positive electrode active materials often inevitably contain alkaline lithium compound impurities (such as lithium carbonate and lithium hydroxide). During the battery cycle, lithium carbonate will produce carbon dioxide and lithium hydroxide will produce water, which also leads to the deterioration of battery cycle stability. When the composite positive electrode material is prepared by the above method 2 or method 3, the alkaline lithium compound remaining in the positive electrode active material can also be consumed (fluorine-containing compounds are more likely to react with alkaline lithium compounds), reducing the content of alkaline lithium compounds, thereby further improving the cycle stability and rate performance of the all-solid-state lithium battery.
[0032] In the present invention, when the above method three is used to prepare the composite positive electrode material, the lithium fluoride layer is coated on the surface of the positive electrode active material particles and the surface of the sulfide solid electrolyte particles at the same time, the lithium fluoride layer has the best protection effect, the interface area between the positive electrode active material and the sulfide solid electrolyte is the largest, and the alkaline lithium compound remaining in the positive electrode active material can be consumed when the lithium fluoride layer is formed. Therefore, the above method three is most preferably used to prepare the composite positive electrode material in the present invention.
[0033] When the composite positive electrode material is prepared by the above method 1, the lithium fluoride layer is only coated on the surface of the sulfide solid electrolyte particles, the protective effect of the lithium fluoride layer and the interface area between the positive electrode active material and the sulfide solid electrolyte are reduced, and the alkaline lithium compounds remaining in the positive electrode active material cannot be consumed.
[0034] When the composite positive electrode material is prepared by the above-mentioned method 2, the lithium fluoride layer is only coated on the surface of the positive electrode active material particles, and the protective effect of the lithium fluoride layer and the interface area between the positive electrode active material and the sulfide solid electrolyte are reduced; however, the alkaline lithium compounds remaining in the positive electrode active material can be consumed when the lithium fluoride layer is formed.
[0035] In some embodiments of the present invention, the fluorine-containing compound is selected from one or more of ammonium fluoride, ammonium bifluoride, lithium hexafluorophosphate, tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride and tetra-n-butylammonium dihydrogen trifluoride.
[0036] Among them, since ammonium fluoride and ammonium bifluoride can decompose to produce hydrogen fluoride gas during the calcination process, and react with the positive electrode active material and the sulfide solid electrolyte in situ, it is helpful to form a thin and uniform lithium fluoride protective layer, further improving the protective effect and interface area. Therefore, the fluorine-containing compound in the present invention is preferably ammonium fluoride and / or ammonium bifluoride.
[0037] In some embodiments of the present invention, the calcination temperature is independently 300-600°C; for example, it can be 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C or 600°C, etc.
[0038] In some embodiments of the present invention, the calcination time is independently 2-10 h; for example, it can be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0039] In some embodiments of the present invention, the heating rate of the calcination is independently 1-5°C / min; for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0040] In some embodiments of the present invention, the calcination is performed in a protective atmosphere.
[0041] In some embodiments of the present invention, the protective atmosphere is an argon atmosphere or a nitrogen atmosphere.
[0042] In a third aspect, the present invention provides a positive electrode plate, comprising the composite positive electrode material as described in the first aspect, or the composite positive electrode material prepared by the preparation method as described in the second aspect.
[0043] In a fourth aspect, the present invention provides an all-solid-state lithium battery, comprising the positive electrode plate as described in the third aspect.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] In the composite positive electrode material provided by the present invention, there is a lithium fluoride protective layer between the positive electrode active material and the sulfide solid electrolyte, which can increase the interface area between the positive electrode active material and the sulfide solid electrolyte while reducing the potential difference between the two and reducing the interface side reactions between the two, so that the all-solid-state lithium battery using the composite positive electrode material of the present invention has good cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The X-ray diffraction spectrum of the composite positive electrode material provided in Example 1 of the present invention;
[0047] Figure 2 A transmission electron microscope image of the composite positive electrode material provided in Example 1 of the present invention;
[0048] Figure 3 X-ray diffraction spectrum of the composite positive electrode material provided in Comparative Example 1 of the present invention;
[0049] Figure 4 This is a rate performance diagram of an all-solid-state lithium battery using the composite positive electrode material provided in Example 1;
[0050] Figure 5 This is a cycle performance diagram of an all-solid-state lithium battery using the composite positive electrode material provided in Example 1;
[0051] Figure 6 This is a rate performance diagram of an all-solid-state lithium battery using the composite positive electrode material provided in Comparative Example 1;
[0052] Figure 7 This is a cycle performance diagram of an all-solid-state lithium battery using the composite positive electrode material provided in Comparative Example 1. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Example 1
[0055] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2, sulfide solid electrolyte Li 5.4 P 1.1 S 4.4 Cl 1.6 , and a lithium fluoride layer formed in situ on the surfaces of both.
[0056] The preparation method of the composite positive electrode material is as follows:
[0057] Weigh LiNi in a mass ratio of 70:29:1 0.6 Co 0.2 Mn 0.2 O2、Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte and ammonium bifluoride were manually ground and mixed for 30 minutes, and then sintered at 400°C for 4 hours in an argon atmosphere at a heating rate of 2°C / min. The product was broken up to obtain a composite positive electrode material.
[0058] Example 2
[0059] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.5 Co 0.3 Mn 0.2 O2, sulfide solid electrolyte Li 10 GeP2S 12 , and a lithium fluoride layer formed in situ on the surfaces of both.
[0060] The preparation method of the composite positive electrode material is as follows:
[0061] Weigh LiNi in a mass ratio of 72:26:2 0.5 Co 0.3 Mn 0.2 O2、Li 10 GeP2S 12 The sulfide solid electrolyte and ammonium fluoride were mixed by roller milling at a rotation speed of 300 rpm, and then sintered at 450°C for 6 hours in an argon atmosphere at a heating rate of 3°C / min. The product was broken up to obtain a composite positive electrode material.
[0062] Example 3
[0063] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, sulfide solid electrolyte Li3PS4, and a lithium fluoride layer formed in situ on the surfaces of the two.
[0064] The preparation method of the composite positive electrode material is as follows:
[0065] Weigh LiNi in a mass ratio of 75:24.5:0.5 0.8 Co 0.1 Mn 0.1O2, Li3PS4 sulfide solid electrolyte and lithium hexafluorophosphate were ball-milled at a speed of 300 rpm, sintered at 500°C for 3 hours in a nitrogen atmosphere at a heating rate of 5°C / min, and the product was broken up to obtain a composite positive electrode material.
[0066] Example 4
[0067] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.9 Mn 0.1 O2, sulfide solid electrolyte Li6PS5Cl, and a lithium fluoride layer formed in situ on the surfaces of the two.
[0068] The preparation method of the composite positive electrode material is as follows:
[0069] Weigh LiNi in a mass ratio of 78:19:3 0.9 Mn 0.1 O2, Li6PS5Cl sulfide solid electrolyte and a mixture of ammonium fluoride and ammonium bifluoride (the mass ratio of ammonium fluoride to ammonium bifluoride is 1:1) are shaken and mixed at 500 times / min, and then sintered at 550°C in a nitrogen atmosphere for 5 hours with a heating rate of 1°C / min. The product is broken up to obtain a composite positive electrode material.
[0070] Example 5
[0071] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.98 Mn 0.02 O2, sulfide solid electrolyte Li7P2S8I, and a lithium fluoride layer formed in situ on the surfaces of the two.
[0072] The preparation method of the composite positive electrode material is as follows:
[0073] Weigh LiNi in a mass ratio of 80:19.8:0.2 0.98 Mn 0.02 O2, Li7P2S8I sulfide solid electrolyte and a mixture of ammonium bifluoride and lithium hexafluorophosphate (the mass ratio of ammonium fluoride to lithium hexafluorophosphate is 5:1) were manually ground and mixed for 1 hour, and then sintered at 600°C for 2 hours in an argon atmosphere with a heating rate of 4°C / min to break up the product to obtain a composite positive electrode material.
[0074] Example 6
[0075] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2, sulfide solid electrolyte Li 5.4 P 1.1 S4.4 Cl 1.6 , and a lithium fluoride layer coated on the surface of the sulfide solid electrolyte.
[0076] The preparation method of the composite positive electrode material is as follows:
[0077] (1) Weigh Li at a mass ratio of 29:1 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte and ammonium bifluoride were manually ground and mixed for 30 minutes, and then sintered at 400°C for 4 hours in an argon atmosphere at a heating rate of 2°C / min to obtain a lithium fluoride-coated sulfide solid electrolyte material;
[0078] (2) Weigh LiNi at a mass ratio of 70:30 0.6 Co 0.2 Mn 0.2 The sulfide solid electrolyte material coated with O2 and lithium fluoride was manually ground and mixed for 30 minutes, and then sintered at 400°C in an argon atmosphere for 4 hours at a heating rate of 2°C / min. The product was broken up to obtain a composite positive electrode material.
[0079] Example 7
[0080] This embodiment provides a composite positive electrode material, including a positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2, sulfide solid electrolyte Li 5.4 P 1.1 S 4.4 Cl 1.6 , and a lithium fluoride layer coated on the surface of the positive electrode active material.
[0081] The preparation method of the composite positive electrode material is as follows:
[0082] (1) Weigh LiNi at a mass ratio of 70:1 0.6 Co 0.2 Mn 0.2 O2 and ammonium bifluoride were manually ground and mixed for 30 minutes, and then sintered at 400°C for 4 hours in an argon atmosphere at a heating rate of 2°C / min to obtain a positive electrode active material coated with lithium fluoride;
[0083] (2) Weigh the positive electrode active material coated with lithium fluoride and Li in a mass ratio of 71:29. 5.4 P 1.1 S 4.4 Cl 1.6The sulfide solid electrolyte was manually ground and mixed for 30 minutes, and then sintered at 400°C for 4 hours in an argon atmosphere at a heating rate of 2°C / min. The product was broken up to obtain a composite positive electrode material.
[0084] Comparative Example 1
[0085] This comparative example provides a composite positive electrode material, and its preparation method is as follows:
[0086] Weigh LiNi in a mass ratio of 70:29:1 0.6 Co 0.2 Mn 0.2 O2、Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte and ammonium bifluoride were manually ground and mixed for 30 minutes to obtain a composite positive electrode material.
[0087] Comparative Example 2
[0088] This comparative example provides a composite positive electrode material, and its preparation method is as follows:
[0089] Weigh LiNi at a mass ratio of 70:30 0.6 Co 0.2 Mn 0.2 O2 and Li 5.4 P 1.1 S 4.4 Cl 1.6 The sulfide solid electrolyte was manually ground and mixed for 30 minutes, and then sintered at 400°C for 4 hours in an argon atmosphere at a heating rate of 2°C / min to break up the product and obtain a composite positive electrode material.
[0090] X-ray diffraction and transmission electron microscopy characterization:
[0091] The composite positive electrode materials provided in the examples and comparative examples were characterized using an X-ray diffractometer and a transmission electron microscope. The X-ray diffraction spectrum of the composite positive electrode material provided in Example 1 is as follows: Figure 1 As shown in the transmission electron microscopy images Figure 2 As shown, the X-ray diffraction spectrum of the composite positive electrode material provided in Comparative Example 1 is as shown Figure 3 shown.
[0092] from Figure 1 It can be seen that lithium fluoride is generated in the composite positive electrode material provided in Example 1; Figure 2 It can be seen that the lithium fluoride layer (the area between the dotted lines) in the composite positive electrode material provided in Example 1 is thin and uniform, with a thickness of about 5 nm. Figure 3 It can be seen that no lithium fluoride is generated in the composite positive electrode material provided in Comparative Example 1.
[0093] Residual alkali Li + Content test:
[0094] 1) Place the positive electrode active material or the composite positive electrode material in a beaker and add deionized water;
[0095] 2) Sealed stirring and dispersing at room temperature;
[0096] 3) Standing and filtering to obtain a clear liquid;
[0097] 4) heating and concentrating the filtered clear liquid;
[0098] 5) Perform acid-base titration with calibrated dilute hydrochloric acid, use methyl orange as the titration endpoint indicator, obtain the titration endpoint, and calculate the total residual Li by the titration endpoint volume. + Content, total residual Li + Content = Total residual Li + Mass / mass of positive electrode active material;
[0099] For the positive electrode active material, the total residual Li + The content is the residual alkali Li before fluorination of the positive electrode active material + content;
[0100] For composite cathode materials, the residual alkali Li after fluorination of the cathode active material + Content = (total residual Li + Mass-Known electrolyte Li + mass) / mass of positive electrode active material.
[0101] Electrochemical performance test:
[0102] The composite positive electrode material provided in the above embodiment and comparative example was pressed on the Li6PS5Cl solid electrolyte layer at a pressure of 180 MPa to obtain a positive electrode sheet in which the composite positive electrode material layer and the electrolyte layer were tightly combined; wherein the surface capacity of the composite positive electrode material layer was 0.5 mAh / cm 2 , the thickness of the solid electrolyte layer is 1 mm;
[0103] The current collector is then pressed onto the composite positive electrode material layer of the positive electrode sheet; a lithium-indium alloy layer and a current collector are placed on the other side of the electrolyte layer and then pressed to obtain an all-solid-state lithium battery.
[0104] The charge and discharge voltage of the all-solid-state lithium battery in Examples 1, 2, 6, 7 and Comparative Examples 1 and 2 is 2.4V-3.7V, and the charge and discharge voltage of the all-solid-state lithium battery in Examples 3, 4, and 5 is 2.4-3.65V. The battery test pressure is 90MPa. Under room temperature conditions, the battery's first charge and discharge efficiency (0.1C), 0.1-1C rate performance, and charge and discharge cycle performance at 1C are tested, where the charge and discharge specific capacity = charge and discharge capacity / mass of the positive electrode active material. The test results are shown in Tables 1 and 2 below.
[0105] The results of the above tests are shown in Table 1 below:
[0106] Table 1
[0107]
[0108] Table 2
[0109]
[0110] Among them, the rate performance and cycle performance of the all-solid-state lithium battery using the composite positive electrode material provided in Example 1 are as follows: Figure 4 and Figure 5 The rate performance and cycle performance of the all-solid-state lithium battery using the composite positive electrode material provided in Comparative Example 1 are shown in Figure 6 and Figure 7 shown. Figure 4 and Figure 6 Among them, the magnification of the 2nd to 6th circles is 0.1C, the magnification of the 7th to 11th circles is 0.2C, the magnification of the 12th to 16th circles is 0.3C, and the magnification of the 17th to 21st circles is 1C.
[0111] From the experimental results in Tables 1 and 2 and Figures 4 to 7 It can be seen that compared with comparative examples 1 and 2 (where no lithium fluoride layer is formed), the composite material provided in Example 1 of the present invention significantly improves the rate performance and cycle performance of the all-solid-state lithium battery.
[0112] Among them, compared with Example 1, since the lithium fluoride layer in Example 6 is only coated on the surface of the sulfide solid electrolyte particles, the protective effect of the lithium fluoride layer and the interface area between the positive electrode active material and the sulfide solid electrolyte are reduced, and the alkaline lithium compounds remaining in the positive electrode active material cannot be consumed. Therefore, the rate performance and cycle performance of the prepared all-solid-state lithium battery are reduced, but it is still better than Comparative Examples 1 and 2.
[0113] Compared with Example 1, in Example 7, since the lithium fluoride layer is only coated on the surface of the positive electrode active material particles, the protective effect of the lithium fluoride layer and the interface area between the positive electrode active material and the sulfide solid electrolyte are reduced. Therefore, the rate performance and cycle performance of the prepared all-solid-state lithium battery are reduced, but still better than Comparative Examples 1 and 2.
[0114] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite positive electrode material, characterized in that: It includes positive electrode active material particles, sulfide solid electrolyte particles and lithium fluoride layer; The lithium fluoride layer is located between the positive electrode active material particles and the sulfide solid electrolyte particles.
2. The composite positive electrode material according to claim 1, characterized in that The lithium fluoride layer is coated on the surface of the sulfide solid electrolyte particles, or coated on the surface of the positive electrode active material particles, or coated on the surface of the positive electrode active material particles and the surface of the sulfide solid electrolyte particles.
3. The composite positive electrode material according to claim 1 or 2, characterized in that: The positive electrode active material is selected from one or more of nickel cobalt manganese oxide and lithium manganese oxide; Preferably, the lithium nickel cobalt manganese oxide is LiNi m Co n Mn 1-m-n O2; Among them, 0.5≤m<1, 0.5≤m+n≤1.
4. The composite positive electrode material according to any one of claims 1 to 3, characterized in that: The sulfide solid electrolyte is selected from compound x(Li a G)·y(T c D d )·z(P2S5) or more; Among them, 0≤x<100, 0≤y<100, 0≤z<100; a=1 or 2, c=1 or 2, d=1, 2 or 5; Element G is S, Cl, Br or I; The element T is Li, Si, Ge, P, Sn or Sb; Element D is Cl, Br, I, O, S or Se; And Li a G.T c D d Unlike P2S5, the stoichiometric numbers of Li and S are not 0.
5. The composite positive electrode material according to any one of claims 1 to 4, characterized in that: The mass ratio of the positive electrode active material to the sulfide solid electrolyte is (50-80):(20-50); Preferably, the mass of fluorine in the lithium fluoride layer accounts for 0.1-2% of the mass of the composite positive electrode material.
6. A method for preparing a composite positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The sulfide solid electrolyte is mixed with a fluorine-containing compound and calcined to obtain a lithium fluoride-coated sulfide solid electrolyte; and then mixed with a positive electrode active material and calcined to obtain the composite positive electrode material; Alternatively, the positive electrode active material is mixed with a fluorine-containing compound and calcined to obtain a positive electrode active material coated with lithium fluoride; and then mixed with a sulfide solid electrolyte and calcined to obtain the composite positive electrode material; Alternatively, the positive electrode active material, the sulfide solid electrolyte and the fluorine-containing compound are mixed and calcined to obtain the composite positive electrode material.
7. The preparation method according to claim 6, characterized in that: The fluorine-containing compound is selected from one or more of ammonium fluoride, ammonium hydrogen fluoride, lithium hexafluorophosphate, tetramethylammonium fluoride, tetraethylammonium fluoride, tetrabutylammonium fluoride and tetra-n-butylammonium dihydrogen trifluoride.
8. The preparation method according to claim 6 or 7, characterized in that: The calcination temperature is independently 300-600°C; Preferably, the calcination time is independently 2-10h; Preferably, the heating rate of the calcination is independently 1-5°C / min; Preferably, the calcination is carried out in a protective atmosphere; Preferably, the protective atmosphere is an argon atmosphere or a nitrogen atmosphere.
9. A positive electrode sheet, characterized in that: It comprises the composite positive electrode material as described in any one of claims 1 to 5, or the composite positive electrode material prepared by the preparation method as described in any one of claims 6 to 8.
10. An all-solid-state lithium battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 9.